Crystal networks in supramolecular gels: formation kinetics and mesoscopic engineering principles. Issue 42 (25th September 2015) - Yu, Rui; Lin, Naibo; Yu, Weidong; Liu, Xiang Yang
Abstract : The formation of crystal networks/patterns is subject to the kinetically favored selection in the process of crystallization. Abstract : For many functional materials, the functionality that is critical to macroscopic behavior begins to manifest itself at the mesoscale. To control the macroscopic properties, knowledge of the structural characteristics in relation to the properties of the mesoscopic materials is crucial. To a large extent, the mesoscopic structure of the crystal networks in supramolecular materials determines the materials' macroscopic properties. This review therefore aims to provide a comprehensive survey of the structural characteristics of crystal networks in correlation with the macroscopic properties/performance and the formation mechanisms of supramolecular gels. In the mesoscopic engineering of soft materials, a strategy constituting a materials engineering triangle is typically adopted. This is applied to engineer soft materials based on a thorough understanding of the correlation between the structure and performance of the materials, as well as the formation kinetics. First, the hierarchy of the crystal network structures, such as the crystal network and domain network, determine the basic key features of crystal networks. Concerning the formation mechanism of the crystal networks, herein, the basic mechanisms of crystal nucleation and growth are first reviewed, and then the review is further extended to the formation of multi-level crystal networks. Consequently, the engineering of mesoscopic materials can be implemented by controlling the crystal network formation. Practical strategies include the application of various stimuli, such as additives, sonication, seeding, and thermodynamic driving force, which allow the tuning and reconstructing of the mesoscopic network structure of supramolecular gels, which leads to a controllable performance of the supramolecular materials. In general, gaining a comprehensive understanding of crystal networks will help in identifying new and robust approaches to engineer and functionalize supramolecular materials in the long term.